The Uslub Tikrar in the Story of Prophet Adam and Its Relevance to Life - Yahya, Ahmad; Mushthoza, Zidna Zuhdana (STKQ Al-Hikam Depok, 2025)
The story of Prophet Adam is a narrative that is often repeated in the Qur'an. This repetition is not a shortcoming but rather an advantage, especially in literary language, where it is known as uslub tikrar or the style of repetition. This article is library-based research using a descriptive-analytical method. This article answers questions related to the form of uslub tikrar in the story of Prophet Adam, its interpretation, and its relevance to life. The results of this study conclude that the style of repetition in the story of Prophet Adam does not focus on only one form. There are three forms of repetition (uslub tikrar): the repetition of verses, sentences, and themes. Furthermore, exegetes explain that uslub tikrar in the story of Prophet Adam is not only for emphasis and beauty but also provides a variety of information to complete the story, which is still general in nature. The repetitive style of the story of Prophet Adam has relevant values for life in embodying the ideal human being, such as piety, introspection, commitment and responsibility, and avoiding arrogance.